Chordoma of the Craniocervical Junction: Endoscopic Endonasal Approach - Voormolen, Eduard H.; Champagne, Pierre Olivier; Froelich, Sebastien (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective This study was aimed to achieve gross-total removal of a chordoma of the craniocervical junction via an endonasal approach (Fig. 1).Design The present study is a case report.Setting The study was conducted at neurosurgical clinic of university hospital.Participant A 40-year-old male, with normal neurologic exam and no prior medical history, presented with a 2-year history of cervicalgia. On preoperative imaging, a midline lesion, with image characteristics of chordoma, was seen in the lower clivus and odontoid. It had limited lateral extension.Main Outcome Measures This study measures postoperative neurological deficits and postoperative tumor volume on magnetic resonance imaging (MRI).Results A binostril approach to the upper nasopharynx was performed using endoscope at 30- and 45-degree angles. Subsequently, a heart-shaped mucosal flap was made and the clivus was drilled to expose the lesion (Fig. 2). After initial debulking, the ring of C1 was slightly drilled to reach the tumor in and around the odontoid. Postoperative MRI showed that a gross-total resection was achieved. The patient had no neurologic deficits postoperatively. Pathologic examination revealed a chordoma of the classical type.Conclusion An endoscopic endonasal approach, utilizing the heart-shaped flap and angled endoscopes and instruments, can be considered for resection of select cases of craniocervical junction chordoma with limited lateral expansion.The link to the video can be found at: https://youtu.be/rwVoZJRBIEo.
Keywords: chordoma; craniocervical junction; endoscopy; endonasal